Public Health Principles Application Failure during Covid-19 Pandemic: Lessons learned and way forward - Qidwai, Waris; Khoja, Tawfik A M; Khoja, Abdullah T (Journal of Liaquat University of Medical & Health Sciences, 2021)
Public Health Principles Application Failure during Covid-19 Pandemic: Lessons learned and way forward